2023
DOI: 10.3390/pharmaceutics15010276
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Pro-Apoptotic Effect of a Cyclic RGD Peptide-Conjugated Magnetic Mesoporous Therapeutic Nanosystem on Hepatocellular Carcinoma HepG2 Cells

Abstract: Numerous nanocarriers have been developed to deliver drugs for the treatment of hepatocellular carcinoma. However, the lack of specific targeting ability, the low administration efficiency, and insufficient absorption by hepatocellular carcinoma cells, severely limits the therapeutic effect of the current drugs. Therefore, it is still of great clinical significance to develop highly efficient therapies with few side effects for the treatment of hepatocellular carcinoma. Herein, we developed a highly effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Modified nMS could deliver drugs into microorganisms and target specific tissue for the responsive release [ 25–29 ]. This study loaded Chx and nAg on the nMS surface or inside the pores (nMS-nAg-Chx), which received synergistic antibacterial effects, providing a potential strategy for drug resistance of Chx long-term use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Modified nMS could deliver drugs into microorganisms and target specific tissue for the responsive release [ 25–29 ]. This study loaded Chx and nAg on the nMS surface or inside the pores (nMS-nAg-Chx), which received synergistic antibacterial effects, providing a potential strategy for drug resistance of Chx long-term use.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, biofilm microenvironments prevent antimicrobial diffusion through the deeper layers of the matrix, which reduces the activity of potent agents [ 24 ]. nMS have been applied as the carrier to deliver drugs into microorganisms and improve antimicrobial performance, which encapsulate agents and target specific tissue to keep a sustained drug concentration in lesion [ 25–29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes demonstrated that the RGDSPIO@MSN@DOX NPs could synergistically increase the death of HepG2 cells and had good stability, biosafety, and drug-loading capability. They also considerably boosted the absorption of DOX by HepG2 cells ( Zhao et al, 2023 ).…”
Section: Classificationmentioning
confidence: 99%